Preparation and characterization of self assembled monolayers of 2-mercaptonicotinic acid on Au(1 1 1) - Pissinis, Diego Ezequiel (2014)
The characterization by cyclic voltammetry, impedance spectroscopy and SERS measurements of 2-mer-captonicotinic acid (2-MNA) monolayers formed under different conditions on Au(111) surfaces, isreported.Self-assembled 2-MNA monolayers on Au(111) in alkaline solutions desorbs reductively from the goldsurface at 0.76 V (vs. ECS). From desorption experiments, the value of the surface concentration wasestimated, resulting similar to that reported for related aromatic molecules.Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) show a rather imperfectblocking behavior of the 2-MNA SAMS. This behavior corresponds to that obtained for microelectrodearrays, which is attributed to the access of ions through pinholes, defects and/or pores present in theSAM.The characteristics of ionisable groups exposed to the solution in the 2-MNA monolayers prepared bydipping in alkaline solutions were obtained by impedance measurements at different pH using the[Fe(CN)6]3 /[Fe(CN)6]4 redox probe and the value of pKa(SAM)for the carboxylate group in the surface2-MNA monolayer was estimated. For pH > pKa, the carboxylic acid group is deprotonated and the mono-layer acquires a negative surface charge, meanwhile it remains neutral or positively charged at lower pHvalues due to the beginning of pyridinic nitrogen protonation, which takes place overlapped with the pro-tonation of the carboxylate group. The protonation of the pyridinic nitrogen is accompanied by desorp-tion of this group from the surface. This leads to a change in the orientation of 2-MNA species allowingthe interaction between the carboxylate group and the gold surface, which was further corroborated fromSERS measurements.In alkaline aqueous medium, 2-MNA adsorbs through a thiolate chemical bond on the gold surface andan additional interaction of the pyridinic nitrogen stabilizes the monolayer. One cathodic peak isobtained when reductive desorption is made in alkaline medium, while a splitting in two cathodic cur-rent contributions for pH values lower than ca. 7 indicates that two different molecular structures coexiston the gold surface in neutral or acidic media. This is assigned to the occurrence of an equilibriumbetween the molecular structure bonded through sulfur and nitrogen and the surface-bonded zwitter-ionic species by intramolecular proton transfer from the carboxylic acid group to the ring nitrogen, lead-ing to the protonation of the pyridinic nitrogen and allowing the interaction of the carboxylate groupwith the gold surface.